A plant-based diet in overweight adults in a 16-week randomized clinical trial: The role of dietary acid load. (August 2021) - Kahleova, Hana; McCann, James; Alwarith, Jihad; Rembert, Emilie; Tura, Andrea; Holubkov, Richard; Barnard, Neal D.
Summary: Background: Evidence suggests that changes in dietary acid load may influence body weight, body composition, and insulin sensitivity. Methods: Participants (n = 244) were randomly assigned to an intervention (vegan) (n = 122) or control group (n = 122) for 16 weeks. Before and after the intervention period, body composition was measured by dual X-ray absorptiometry. Insulin resistance was assessed with the Homeostasis Model Assessment (HOMA-IR) index and predicted insulin sensitivity index (PREDIM). Repeated measure ANOVA was used for statistical analysis. Results: Potential Renal Acid Load (PRAL) and Net Endogenous Acid Production (NEAP) decreased significantly in the vegan group with no change in the control group (treatment effect −24.7 mEq/day [95% CI -30.2 to −19.2]; p < 0.001; and −23.8 mEq/day [95% CI -29.6 to −18.0]; p < 0.001, respectively). Body weight decreased by 6.4 kg in the vegan group, compared with 0.5 kg in the control group (treatment effect −5.9 kg [95% CI -6.8 to −5.0]; Gxt, p < 0.001), largely due to a reduction in fat mass and visceral fat. HOMA-IR index decreased and PREDIM increased in the vegan group. After adjustment for energy intake, changes in PRAL and NEAP correlated positively with changes in body weight (r = +0.37; p < 0.001; and r = +0.37; p < 0.001, respectively), fat mass (r = +0.32; p < 0.001; and r = +0.32; p < 0.001, respectively), visceral fat (r = +0.19; p = 0.006; and r = +0.15; p = 0.03, respectively), and HOMA (r = +0.17; p = 0.02; and r = +0.20; p = 0.006, respectively), and negatively with changes in PREDIM (r = −0.22; p = 0.002; and r = −0.27; p < 0.001, respectively). Conclusion: Dietary acid load as part of a plant-based diet was associated with changes in body weight, body composition, and insulin sensitivity, independent of energy intake. Mechanistic explanations suggest that the relationship may be causal. Trial registration: ClinicalTrials.gov number, NCT03698955.